Joseph Godwin Greenfield: The father of neuropathology (1884-1958) - Kalyan B Bhattacharyya (Annals of Indian Academy of Neurology, 2015)
The systematic study of neuropathology was initiated by Godwin Greenfield in the early part of the 20 th century. He worked at the National Hospital, Queen Square, London for the major period of his life and worked on various subjects like cerebrospinal fluid, intracranial tumours, cerebellar ataxias, dystrophia myotonica, disseminated sclerosis, subacute combined degeneration of the spinal cord, and the like. After his retirement he visited the National Institute of Neurological Diseases and Blindness in Bethesda, Maryland, USA, from time to time and there he died suddenly from myocardial infarction.